1968
DOI: 10.1002/zaac.19683570302
|View full text |Cite
|
Sign up to set email alerts
|

Über den Hedvall‐Effekt. I. Die Reaktion von Bariumoxid mit Silberjodid

Abstract: Die Reaktion von BaO mit AgJ, die häufig als Beispiel für den HEDVALL‐Effekt angeführt wird, läßt sich bei sorgfältigem Ausschluß von Feuchtigkeit und CO2 der Luft nicht nachweisen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1970
1970
1983
1983

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The second edition of Songina's monograph ( 236) is a welcome contribution to the literature of amperometric titrations. Several accounts of electroanalytical methods include such titrations (1,13,29,51,109,110,229,257).…”
Section: Apparatus and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The second edition of Songina's monograph ( 236) is a welcome contribution to the literature of amperometric titrations. Several accounts of electroanalytical methods include such titrations (1,13,29,51,109,110,229,257).…”
Section: Apparatus and Methodologymentioning
confidence: 99%
“…TGA has been applied to the reaction of BaO and Agí and it was shown that the Hedvall effect was not observed if contamination by atmospheric H20 and C02 was prevented (109). Among the oxides studied by TGA have been U3Os (170), Pb02 (267), and NiO, CoO, Fe203, and Cr203 with H2 and CO (281).…”
mentioning
confidence: 99%
“…Since the alkaline earth metal oxides are strongly hygroscopic, this constancy of the temperature at which interaction starts led some investigators to suggest that Hedvall and Tamman had used hydroxide-contaminated oxides whose melting points were rather low, and the interaction had been brought about by the presence of a liquid phase [4,5]. A number of attempts were made [6][7][8] to reproduce the Hedvall effect. Some of these ended in failure, as was the case with calcium and magnesium oxides for instance [8].…”
mentioning
confidence: 98%